2000 Kansas Performance Tests with Winter Wheat Varieties - Roozeboom, Kraig L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
The Kansas Agricultural Experiment Station annually compares both new and currently grown varieties in the state’s major crop-producing areas. These performance tests generate unbiased performance information designed to help Kansas growers select wheat varieties suited for their area and conditions.
Keywords: Wheat; Crop development; Diseases; Weather; Insects; Statistics; Kansas